ANALISIS KOMPARATIF SANKSI PIDANA MATI ANTARA HUKUM PIDANA INDONESIA DAN MALAYSIA - Rai Iqsandri, (Proceeding International Conference on Social Sciences, 2026)
The death penalty has been abolished in many countries worldwide, while some still retain it in their legal systems but remain inactive in its implementation. Conversely, certain nations continue to actively enforce capital punishment. This study conducts a comparative legal analysis of death penalty sanctions in Indonesia and Malaysia, emphasizing their legal foundations, implementation, and policy directions. The death penalty represents the most severe criminal sanction and continues to generate debates between the principles of justice and the protection of human rights. Employing a normative juridical method and a comparative approach, this research analyzes statutory laws, legal doctrines, and criminal policy frameworks in both countries. The findings reveal that Indonesia maintains the death penalty as a principal punishment but redefines it under the 2023 Criminal Code as a conditional sentence with a ten-year probationary period before execution. In contrast, Malaysia has undertaken major legal reforms by abolishing the mandatory death penalty in 2023, granting judges the discretion to impose alternative sanctions such as life imprisonment. This comparative study highlights how both countries are moving toward more humanistic and proportionate criminal justice systems, reflecting global trends in the reform of capital punishment